"Crumpled" filter has the potential to slash energy consumption in industry. Issue 10 (October 2015) - Unknown
Abstract : Scientists in the UK at Imperial College London have developed an ultra-thin, super-strong membrane to filter liquids and gases. They say it has the potential to cut energy consumption in industry, as this brief article explains.